Origin and distribution of femoral nerves in swine (Sus scrofa domesticus) fetuses from crosses of Dan Bred and AGPIC-337 lines - Gustavo Cavinato Herrera; Frederico Ozanam Carneiro e Silva; Lázaro Antônio dos Santos; Lorena Tannus Menezes; Flávio Machado de Moraes (Bioscience Journal, 2018)
The objective of this work was to assess the origin and distribution of femoral nerves in 30 swine fetuses from crosses of Dan Bred and AGPIC-337 lines. Thirty animalsâ€”fifteen males and fifteen femalesâ€”from the collection of the Faculty of Veterinary Medicine's Animal Anatomy Laboratory of the Federal University of Uberlândia, Uberlândia MG, Brazil, were used. The animals were fixed by injecting a 10% aqueous formaldehyde solution into the descending aorta artery and thoracic, abdominal, pelvic and intramuscular cavities. The specimens were then submerged in a solution with the same concentration. These animals have five to seven lumbar vertebrae. The number of lumbar vertebrae was six in 96.67% and seven in 3.33% of the animals. The femoral nerve originated from the L4 and L5 (66.67%), L5 and L6 (26.67%) and L3 and L4 (6.66%) lumbar vertebrae. It sent branches to the psoas major, psoas minor, iliac, pectineus, and quadriceps femoris muscles in all animals, to the sartorius in 43.33% and to the gracilis in 6.66% of animals. No marked differences were found in the characteristics of origin and distribution of the femoral nerve between the swine fetuses from crosses of Dan Bred and AGPIC-337 lines and the animals described in the literature.